2016
DOI: 10.1016/j.anorl.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

CSF Gusher in Cochlear Implant Surgery–does it affect surgical outcomes?

Abstract: a b s t r a c tObjectives: The purpose of this prospective study was to measure surgical outcomes in cases of cerebrospinal fluid gusher in cochlear implant surgery. Materials and methods: Demographic, radiological, neurophysiological and surgical results were evaluated in nine cases of patients with cerebrospinal fluid gusher during cochlear implant surgery, out of 164 unilateral cochlear implant procedures. Review of literature and our management technique is discussed. Results: Nine cases had cerebrospinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…CSF gusher increases the infection risk and the failure rate of surgery [Eisenman et al, 2001;Arnold et al, 2002;Sennaroglu, 2010;Hongjian et al, 2012;Vashist and Singh, 2016]; however, certain previous studies have not linked gusher to worse postoperative hearing outcomes [Lee et al, 2010;Adunka et al, 2012]. It has also been previously asserted, though not quantified, that gusher is associated with poorer speech understanding and poorer receptive vocabulary acquisition [Hongjian et al, 2012].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CSF gusher increases the infection risk and the failure rate of surgery [Eisenman et al, 2001;Arnold et al, 2002;Sennaroglu, 2010;Hongjian et al, 2012;Vashist and Singh, 2016]; however, certain previous studies have not linked gusher to worse postoperative hearing outcomes [Lee et al, 2010;Adunka et al, 2012]. It has also been previously asserted, though not quantified, that gusher is associated with poorer speech understanding and poorer receptive vocabulary acquisition [Hongjian et al, 2012].…”
Section: Discussionmentioning
confidence: 98%
“…Though previously suggested as a cause of gusher, the cochlear aqueduct is likely not big enough to facilitate the volume of fluid egress associated with CSF gusher [Gopen et al, 1997;Tekdemir et al, 2000]. Similarly, it could be assumed that all of the patients in the nongusher group had an intact internal auditory canal and modiolus [Sennaroglu, 2010;Farinetti et al, 2014;Vashist and Singh, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…The CAP score is an index describing the highest typical level of functional hearing in everyday life. This scale can provide brief information about speech and conversation performance of CI patients [29]. Bhadania, et al [13] used CAP scale to interpret their results of CI revision surgery and found good performance in postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente, otro aspecto de gran relevancia es el pronóstico, tanto en cuanto a la cirugía (morbilidad asociada) como al desempeño del paciente. En relación con el pronóstico quirúrgico, un trabajo realizado por Vashist 8 encontró que, en un grupo de nueve pacientes que presentaron gusher y que fueron manejados con sellado del sitio de cocleostomía con fascia y periostio, ninguno ameritó medidas extraordinarias para el manejo del gusher, y los autores concluyen que un sellado cuidadoso del sitio de cocleostomía y una vigilancia adecuada son suficientes para prevenir la morbilidad asociada al procedimiento quirúrgico. En lo que se refiere al desempeño del lenguaje de estos pacientes, hay que considerar que un porcentaje importante también presentan comorbilidad neurológica.…”
Section: Discussionunclassified